The effect of the Ayas model to learning individual fast attack and high-order thinking skills of handball for students - Hussein, Ali Radhi Abdul (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. The significance of this research lies in designing a specialized scale to evaluate advanced cognitive skills related to handball among students. It also examines the impact of the Ayas model on enhancing these higher-order thinking skills and teaching the technique of the individual fast attack in handball. This study aimed to investigate the effect of the Ayas Model on learning individual fast attack techniques and higher-order thinking skills in handball among students.Material and Methods. The experimental method was adopted, involving a sample of 64 third-year students from the College of Physical Education and Sports Sciences at the University of Babylon. The sample was divided into two groups: an experimental group (32 students), taught using the Ayas Model, and a control group (32 students), taught using traditional methods. Pre- and post-tests were conducted to assess the students"™ performance in individual fast attack techniques and higher-order thinking skills. . Analysis was assisted using the SPSS application.Results. The results revealed significant improvements in both groups, with the experimental group demonstrating substantially higher progress. Statistical analysis confirmed the superiority of the Ayas Model in enhancing both technical and cognitive skills, with calculated t-values indicating significant differences in favor of the experimental group (p < 0.05). These findings suggest that the Ayas Model is an effective pedagogical approach for improving students"™ technical proficiency and cognitive abilities in handball.Conclusion. The study concludes that integrating interactive, student-centered learning methods can enhance sports education outcomes and promote holistic skill development. This research provides a theoretical and practical foundation for educators and coaches to integrate interactive and student-centered learning approaches to holistically improve physical education outcomes.